PENGARUH PROFITABILITAS, KEBIJAKAN DIVIDEN, KEPUTUSAN INVESTASI DAN KEPUTUSAN PENDANAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN HEALTHCARE YANG TERDAFTAR DI BURSA EFEK INDONESIA PEIRODE 2019-2023 - Puspitasari, Endah Rifka; Arief, Abubakar (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstrak: This study aims to analyze the effect of profitability, dividend policy, investment decisions, and financing decisions on firm value in healthcare companies listed on the Indonesia Stock Exchange (IDX) for the period 2019-2023. The research sample consists of 14 companies selected using purposive sampling technique. The data used is secondary data in the form of annual financial statements obtained from the Indonesia Stock Exchange. The analysis method employed is multiple regression analysis using SPSS. The results indicate that profitability, dividend policy, investment decisions, and financing decisions simultaneously have a positive and significant effect on firm value. Partially, each inDependent Variable also shows a significant positive impact on firm value. This research model explains 89.2% of the variation in firm value, while the remaining variation is influenced by other factors not examined in this study. This research provides important implications for company management, investors, and other stakeholders to pay attention to factors that can enhance firm value in the pharmaceutical sector.Keywords: Profitability, Dividend Policy, Investment Decisions, Funding Decisions, Firm Value, Pharmaceutical Sector